UPAYA PENINGKATAN PENGUASAAN KOSA KATA BAHASA INDONESIA MENGUNAKAN GAME INTERACTY EDUCATION DI KELAS II SDN 112/I PERUMNAS - Patra, Ridho; Syarif, Ahmad; Budiono, Hendra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe efforts to improve Indonesian vocabulary mastery through the use of Interacty Education Games for second-grade students at SDN 112/I Perumnas. This research employed a mixed-method approach with Classroom Action Research (CAR) conducted in two cycles, each consisting of two meetings. The subjects of the study were 18 second-grade students. Data collection techniques included observation and tests, while data analysis involved the stages of data presentation and conclusion drawing, using triangulation techniques to ensure data validity. The results showed that the application of Interacty Education Games was able to improve students' Indonesian vocabulary mastery gradually and sustainably. In the pre-action stage, the classical vocabulary mastery score was at 51.6% (Category D). After the action in Cycle I, the classical score increased to 56.8% in the first meeting and rose further to 61.1% in the second meeting. A more significant improvement occurred in Cycle II, where the classical score reached 65.4% in the first meeting and increased optimally to 77.9% in the second meeting. This improvement indicates that Interacty Education Games are effective in enhancing students' engagement, learning motivation, and understanding of Indonesian vocabulary.